Ketogenic diet in childhood epilepsy: clinical algorithm in a tertiary care center - Shaaban, Sanaa; Al-Beltagi, Mohammed; El Rashidy, Omnia; Nassar, May; El Gendy, Yasmin (Frontiers in Pediatrics, 2023)
Background: Dietary therapies play a crucial role in managing patients with specific types ‎of epilepsy and those who display adverse effects or not responding to pharmacological ‎treatments. The ketogenic diet (KD) is a high-fat, restricted carbohydrate, and adequate ‎protein regimen. The KD has proven to be an effective non-pharmacological treatment for ‎drug-resistant epilepsy (DRE) by generating ketones that act as an alternative fuel source ‎for the brain, thereby reducing the occurrence of seizures. The advantages of KD have been ‎attributed to its universal availability, numerous administration techniques, and ‎affordability. Objective: This article presents the KD algorithm developed by a ‎multidisciplinary team of experts at the Children's Hospital, Ain Shams University, Egypt. ‎The algorithm serves as a guide for implementing the KD in treating DRE in ‎children. The algorithm has been previously validated through a study. Methods: The ‎algorithm consists of seven essential stages: 1) Referral of patients to the Complex Epilepsy ‎Committee, 2) Pre-diet assessment of patients, 3) Referral of patients to the Clinical ‎Nutrition (CN) team, 4) Diet selection and initiation, 5) Seizure follow-up and diet fine-tuning, 6) Diet reassessment after three months, and 7) Evaluation of the KD journey after ‎‎24 months. Results: The KD algorithm was systematically developed and proved highly ‎influential in facilitating the implementation of the KD. The algorithm yielded significant ‎health benefits in pediatric patients. Conclusion: The KD algorithm provides a systematic ‎approach to implementing the ketogenic diet and has demonstrated positive health ‎outcomes in pediatric patients. ‎